(untitled) (Philological Studies, 2022)
South Slavic oral lyric songs model the relations between people and animals in analogies and contrasts, showing the similarities and differences between them. People and animals are seen as different when their worlds, nature, and culture, wild and tame are confronted. On the other hand, when the heroes and heroines of the songs are in positions of the Other, the alien, then the similarities between them and the animals are emphasized. The oral lyric songs sing about complex relations between people and animals – they reveal mythic matrixes (the motif of the golden hair maiden, deer, and fish as a triple catch), patterns of hospitality and wedding rituals, as well as the utopian fragments of desire for freedom. The relations between people and animals reveal a multi-layered worldview and the variety of ways of experiencing that world and the beings that inhabit it – in moments of encounters and crisis.